Adipose-derived mesenchymal stem cells and extracellular vesicles confer antitumor activity in preclinical treatment of breast cancer. (July 2020) - Li, Tao; Zhou, Xiaohe; Wang, Jingzhe; Liu, Ziyao; Han, Sen; Wan, Lu; Sun, Xiaochun; Chen, Huabiao
Graphical abstract: Abstract: Both antitumor and protumor property of mesenchymal stem cells (MSCs) have been demonstrated. We hypothesize that this contradiction is due to the heterogeneity of MSC subsets and that extracellular vesicles (EVs) from distinct MSC subsets can transfer the corresponding antitumor activities. Here we evaluated the antitumor activities of two subsets of adipose-derived mesenchymal stem cells (ADSCs) and ADSC-derived EVs (ADSC-EVs) in immunocompetent syngeneic mouse models of breast cancer. We identified CD90 high and CD90 low ADSC subsets and demonstrated that CD90 high ADSCs could be converted into CD90 low ADSCs by stimulation with LPS. CD90 low ADSCs and its derived EVs significantly inhibited tumor growth in tumor-bearing mice. Benefit of tumor control were associated with decreased tumor cell proliferation and migration, and enhanced tumor cell apoptosis mediated by ADSC-EVs. Antioncogenic miRNA-16-5p loaded CD90 low ADSC-EVs further significantly enhanced antitumor activities. Taken together, this study represents the first attempt to apply our newly identified antitumor ADSCs and its derived EVs in preclinical treatment of breast cancer. This study also provides the evidence that EVs can serve as a novel and effective therapeutics or drug delivery vesicle. This new therapeutic approach could be potentially applicable to breast cancer and many other types of cancer.